Lower extremity range of motion and alignment: A reliability and concurrent validity study of goniometric and three-dimensional motion analysis measurement. Issue 8 (August 2020) - Ore, Viktor; Nasic, Salmir; Riad, Jacques
Abstract: Background: Knowing correlations between passive goniometric and dynamic three-dimensional motion analysis measurements of lower extremity range of motion and alignment would benefit knee injury risk assessment. Purpose: To investigate reliability and concurrent validity of lower extremity assessment with goniometry and three-dimensional motion analysis. Methods: Thirty-eight participants (76 limbs) were examined in standardized positions by two physiotherapists with simultaneous goniometric and three-dimensional motion analysis measurements of passive range of motion and alignment. Intra-class correlation coefficient (ICC) and median differences were calculated. Results: Hip rotation reliability, ICC 0.74–0.89 and validity 0.74–0.94. Tibial rotation reliability, ICC 0.24–0.75 and validity 0.08–0.61. Knee extension reliability, ICC 0.44–0.73 and validity 0.22–0.60. Knee valgus/varus reliability, ICC 0.36–0.68 and validity 0.25–0.62. Tibial torsion reliability, ICC 0.52–0.77 and validity 0.58–0.81. Ankle dorsiflexion reliability, ICC 0.12–0.73 and validity 0.51–0.83. Median differences in reliability and validity ranged from -2.0° to 3.0° and from -6.6° to 7.5° respectively. Conclusion: Goniometric and three-dimensional motion analysis methods define the lower body segments differently making some degree of discrepancy in the measurements inevitable. Nevertheless, the variables chosen in this study are all strongly associated with anterior cruciate ligament rupture and some may prove useful to identify individuals at risk of knee injury during sport activities. Study design: Cross-sectional laboratory study. Abstract : Anatomy; Clinical Research; Rehabilitation; Diagnostics; Health Promotion; Health Technology; Goniometer, Three-dimensional motion analysis, reliability, concurrent validity, knee injury, anterior cruciate ligament rupture